2013
DOI: 10.1038/srep01517
|View full text |Cite
|
Sign up to set email alerts
|

The 3-D reconstruction of medieval wetland reclamation through electromagnetic induction survey

Abstract: Studies of past human-landscape interactions rely upon the integration of archaeological, biological and geological information within their geographical context. However, detecting the often ephemeral traces of human activities at a landscape scale remains difficult with conventional archaeological field survey. Geophysical methods offer a solution by bridging the gap between point finds and the surrounding landscape, but these surveys often solely target archaeological features. Here we show how simultaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…The presence of both PERP and HCP coil arrangements in the Dualem‐21S allows it to simultaneously record eight output signals, creating a large EM dataset that has proved useful for the analysis, reconstruction and modelling of soil profiles for complex multi‐layered Holocene deposits at variable depth, particularly when supplemented by augering (Simpson et al ., ). From an archaeological‐feature perspective the instrument has produced promising apparent magnetic susceptibility results comparable to magnetometer data (De Smedt et al ., , ) and apparent electrical conductivity data that correspond well with excavation data (Saey et al ., ). Recent work has shown that the Dualem surveys were able to identify a variety of archaeological features, including 2m‐wide ring ditches (Simpson et al ., ), a large (12 m wide) moat (Saey et al ., ) and brick block foundations ca.…”
Section: Electromagnetic Surveyssupporting
confidence: 79%
See 1 more Smart Citation
“…The presence of both PERP and HCP coil arrangements in the Dualem‐21S allows it to simultaneously record eight output signals, creating a large EM dataset that has proved useful for the analysis, reconstruction and modelling of soil profiles for complex multi‐layered Holocene deposits at variable depth, particularly when supplemented by augering (Simpson et al ., ). From an archaeological‐feature perspective the instrument has produced promising apparent magnetic susceptibility results comparable to magnetometer data (De Smedt et al ., , ) and apparent electrical conductivity data that correspond well with excavation data (Saey et al ., ). Recent work has shown that the Dualem surveys were able to identify a variety of archaeological features, including 2m‐wide ring ditches (Simpson et al ., ), a large (12 m wide) moat (Saey et al ., ) and brick block foundations ca.…”
Section: Electromagnetic Surveyssupporting
confidence: 79%
“…Recent work has shown that the Dualem surveys were able to identify a variety of archaeological features, including 2m‐wide ring ditches (Simpson et al ., ), a large (12 m wide) moat (Saey et al ., ) and brick block foundations ca. 1 m 2 (De Smedt et al ., ). The large Tx/Rx coil separation strongly influences the depth penetration and response pattern, currently suggesting that the towed Dualem system is very well suited to large landscape studies analysing soil components; the relatively large volumes of soil investigated, however, suggests that smaller scale features are less likely to be mapped.…”
Section: Electromagnetic Surveysmentioning
confidence: 97%
“…The combined analyses of σ a and κ a of multi‐receiver EMI sensors now allows composing integral reconstructions of human environments, taking into account both the past natural and anthropological variations (e.g. De Smedt et al ., ). However, the main aim of these studies has been on combining and analysing the multiple σ a measurements.…”
Section: Introductionmentioning
confidence: 97%
“…The errors introduced by the LIN approximation are discussed in detail in Materials and Methods. The LIN approximation has been used by several authors, such as Santos [20], who created a laterally-constrained inversion routine, and it has also seen use in archaeological applications [21,22]. The approach by Santos was lately developed further to a quasi-3D approach, but still under the LIN approximation [23].…”
Section: Introductionmentioning
confidence: 99%